Public research and development in European union countries - evaluation based on selected indicators - Halásková, Martina; Bednář, Pavel (Univerzita Pardubice, 2018)
Research, development and innovation hold a prominent position in national economies and the public sector. The aim of the paper is to evaluate the role of public research in EU countries with focus on selected indicators of research and development (R&D). The area in focus is total R&D expenditures and public R&D expenditures in years 2010 and 2015. The author also strives to analyze other R&D indicators in EU countries, pointing out the similarities and differences in the particular countries. The analysis concentrates on not only the selected indicators of public R&D, but also a comprehensive evaluation and role of public research in EU countries. EU countries are evaluated on the basis of indicators of public R&D by means of factor analysis, cluster analysis and box-plot, divided into four clusters depending on internal similarity in 2015. The most marked differences were observed in indicators of public research (R&D public expenditures as % of total R&D expenditures, researchers in public sector as % of total researchers, number of publications per 1000 researchers in the public sector, number of citable publications per 1000 researchers in the public sector) in the first cluster in comparison to the third cluster. In case of the indicator H-index (per 1000 researchers in the public sector) the most marked differences were observed in most countries of the second cluster in comparison to countries of the fourth cluster.
Keywords: research and development; public R&D; R&D public expenditure; indicators of R&D; EU countries; H54; H76; O32